Extreme Intellectual Ability and the Dynamics of Social Inclusion - Persson, Roland S. (International Journal for Talent Development and Creativity, 2020)
While it is easy to include gifted into society individuals representing the social functions of maintenance or entertainment, it is much more challenging to fully include brilliant intellectuals, who can potentially change society and its power structure by their insights. This paper presents the theory and research underpinning various aspects social evolutionary dynamics in relation to many years of giftedness and talent scholarship to understand the dynamics of social inclusion; and the social inclusion of gifted and talented individuals in particular. As based on well-established empirical research from a multitude of disciplines, the conclusion of this paper was that societal attitudes toward the intellectually gifted may, to some extent, certainly be influenced for the better by social policy as well as by the education of the general public. However, importantly, existing research suggested that educating the gifted and talented themselves is also necessary. They too need an understanding of who they are in the light of social evolutionary dynamics; they need to learn why the world around them sometimes reacts aversively even though they are brilliant, and generally benevolent and socially responsible and they constitute considerable, yet often ignored, assets to all of society as a whole.